To the Question of the Elaboration of the Strategy for the Shanghai Cooperation Organization - V. J. Vorobyov (Vestnik MGIMO-Universiteta)
Working out of a development strategy for the SCO largely depends on the constantly changing international environment, the political instability of member-states and the group’s plans to include new members. Mid-term planning will allow the SCO to give an effective and timely response to both internal and external challenges, set attainable goals and correct the existing shortcomings such as the lack of an efficient mechanism of action in times of crises. To establish such a mechanism the SCO should reconsider the consensus voting principle on a number of questions and actively use the emergency sessions of the SCO ruling bodies.